2004
DOI: 10.1007/s00417-004-0945-4
|View full text |Cite
|
Sign up to set email alerts
|

The age-dependent decrease in the myogenic response of retinal arterioles as studied with the Retinal Vessel Analyzer

Abstract: Studies on autoregulation in retinal disease should consider the normal age-related decrease in diameter response of retinal arterioles when the blood pressure is changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 22 publications
6
52
1
Order By: Relevance
“…In our study we showed an association between flicker response and age; however, the coefficient of correlation was weak, which is in agreement with previous reports (30). For example, Jeppesen et al (31) reported significantly reduced diameter response in normal individuals aged Ͼ40 years.…”
Section: Discussionsupporting
confidence: 93%
“…In our study we showed an association between flicker response and age; however, the coefficient of correlation was weak, which is in agreement with previous reports (30). For example, Jeppesen et al (31) reported significantly reduced diameter response in normal individuals aged Ͼ40 years.…”
Section: Discussionsupporting
confidence: 93%
“…The observed vasoconstriction secondary to isometric exercise at baseline was comparable to previous observations in normal persons [10,22], confirming that pressure autoregulation is preserved in diabetic patients without retinopathy [23], and is in accordance with the GF around 1 as calculated from the resting diameters. The reduced vasoconstriction during hypoxia was in accordance with results from a study in normal persons [11], but may depend on the degree of hypoxia since a similar response was neither found in a study with a verified lower degree of hypoxia [10] nor in a study where a lower oxygen saturation was intended but in which a <2% contraction of retinal arterioles was achieved, and the accompanying changes in the arterial blood pressure were not monitored [3].…”
Section: Discussionsupporting
confidence: 77%
“…The lack of predictive value of age on the therapeutic outcome may be due to an increased stiffening of the retinal vascular walls with age that hinders dilatation when the blood pressure increases. 25 The findings of the present study are limited by several factors. Thus, the measurements of oxygen saturation and diameters in the larger retinal vessels were not performed repeatedly, and, therefore, an influence of dynamic properties of vascular function to the observed effects may have been overlooked.…”
Section: Discussionmentioning
confidence: 90%